2022
DOI: 10.3389/fmed.2021.818647
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Drug Approval as a Path to Market for Oncology Drugs in Canada: Challenges and Recommendations for Assessing Eligibility and Regulatory Responsiveness

Abstract: International drug regulators use conditional drug approval mechanisms to facilitate faster patient access to drugs based on a lower evidentiary standard typically required of drug approvals. Faster and earlier access is justified by limiting eligibility to drugs intended for serious and life-threatening diseases and by requiring post-market evidence collection to confirm clinical benefit. One such mechanism in Canada, the Notice of Compliance with Conditions (NOC/c) policy, was introduced in 1998. Today, most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…However, the extent of the benefit/MTA over other medicinal products cannot be assessed. Similar observations have recently been reported for the Canadian counterpart of CMA, the Notice of Compliance with Conditions (NOC/c) 32 . Specific obligations that require (often randomized) postauthorization clinical studies should ultimately resolve these uncertainties and confirm the positive benefit–risk balance.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, the extent of the benefit/MTA over other medicinal products cannot be assessed. Similar observations have recently been reported for the Canadian counterpart of CMA, the Notice of Compliance with Conditions (NOC/c) 32 . Specific obligations that require (often randomized) postauthorization clinical studies should ultimately resolve these uncertainties and confirm the positive benefit–risk balance.…”
Section: Discussionsupporting
confidence: 71%
“…Similar observations have recently been reported for the Canadian counterpart of CMA, the Notice of Compliance with Conditions (NOC/c). 32 Specific obligations that require (often randomized) postauthorization clinical studies should ultimately resolve these uncertainties and confirm the positive benefit-risk balance. However, many of the confirmatory trials for the conditionally authorized medicinal products in our study cohort are still ongoing.…”
Section: Articlementioning
confidence: 99%
“…At least one-third of the potential information about patient trial characteristics and the benefits and risks of tested treatments was missing [ 11 ]. McPhail and colleagues concluded that eligibility criteria for oncology drugs to qualify for a NOC/c are insufficiently defined, resulting in their inconsistent application by Health Canada [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to better use of Japan’s potentially advantageous requirement for a postapproval reexamination of oncology drugs, every country could make better use of the much-discussed but inadequately implemented concept of conditional approval . Ideally, a regulatory body could use a surrogate measure to give a drug quick provisional authorization for use in a limited way, during which time it would be available but subjected to ongoing study.…”
mentioning
confidence: 99%
“…In addition to better use of Japan's potentially advantageous requirement for a postapproval reexamination of oncology drugs, every country could make better use of the much-discussed but inadequately implemented concept of conditional approval. 10 Ideally, a regulatory body could use a surrogate measure to give a drug quick provisional authorization for use in a limited way, during which time it would be available but subjected to ongoing study. After a few years of such use, the systematically collected evidence would be reviewed and a decision made about whether to grant full approval, or, if the drug still has not been shown to provide meaningful clinical benefit, as occurred disturbingly often in the trials reviewed by Maeda at al, 1 its conditional approval could be withdrawn until such time as it can be shown to actually help patients.…”
mentioning
confidence: 99%